Konsep Pendidikan Islam Dalam Kitab Fathul Baari - Minggusta Juliadarma (eL Bidayah: Journal of Islamic Elementary Education, 2019)
The concept of Islamic education is absolutely necessary in forming Muslims who are pious, noble and have good cognitive abilities. For this reason, many Islamic thinkers try to formulate the concept of Islamic education as a whole which can be used as a reference in fostering the younger generation of Islam. Islamic thinkers include: Ibn Hazm, al-Ghazali, an-Nahlawi, Naguib al-Attas and others. In this paper, the author tries to present other nuances from a different perspective, the author tries to uncover the concept of Islamic education According to the hadith scholars, namely Ibn Hajar al-Asqalani in the book Fathul Baari. The research in this paper aims to: (1) To know the concept of Islamic education in the book Fathul Baari, and (2) To find out the differences in the concept of Islamic education in the book Fathul Baari with the concept of other Islamic education. the concept of Islamic education in the book contains the definition of education, the position of science in Islamic education, educators and their duties, and methods of education.